2009
DOI: 10.1021/jp901225y
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of the Early 3d Transition Metal Diatomic Chlorides and Their Ions, ScCl0,±, TiCl0,±, VCl0,±, and CrCl0,±

Abstract: The titled molecular species have been studied by ab initio multireference and coupled-cluster methods in conjunction with large correlation consistent basis sets. A total of 71 MCl, 13 MCl(+), and 9 MCl(-) states, M = Sc, Ti, V, Cr, have been examined. We report total energies, dissocation energies, spectroscopic parameters, and full potential energy curves. Most of our results are presented for the first time in the literature, whereas the general agreement with available experimental data can be considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
(159 reference statements)
3
15
0
Order By: Relevance
“…For ScCl, it has been suggested that the reference experimental value (BDE of 341.1 kJ mol –1 ) is too low, as indicated by an alternative high-level theoretical value of 447.7 kJ mol –1 . We note that several of the best performing DFTs, for example, ωB97M-V and MN15, show large positive deviations for ScCl (+99.6 and +107.3 kJ mol –1 , respectively).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…For ScCl, it has been suggested that the reference experimental value (BDE of 341.1 kJ mol –1 ) is too low, as indicated by an alternative high-level theoretical value of 447.7 kJ mol –1 . We note that several of the best performing DFTs, for example, ωB97M-V and MN15, show large positive deviations for ScCl (+99.6 and +107.3 kJ mol –1 , respectively).…”
Section: Resultsmentioning
confidence: 72%
“…For ScCl, it has been suggested that the reference experimental value (BDE of 341.1 kJ mol −1 ) is too low, 28 as indicated by an alternative high-level theoretical value of 447.7 kJ mol −1 . 62 We note that several of the best performing DFTs, for example, ωB97M-V and MN15, show large positive deviations for ScCl (+99.6 and +107.3 kJ mol −1 , respectively). Most of the DFT methods examined also yield BDEs that are significantly larger than the experimental value; the mean deviation (MD) for the 29 DFT methods is +111.2 kJ mol −1 , which is virtually identical in magnitude to the MAD.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 78%
“…The calculated bond distances and frequencies were extrapolated to the CBS level by extrapolating the individual energies from the seven-point fits at the Q5 level. For TiCl, VCl, and CrCl, Kardahakis and Mavrides provide a good overview of experimental and computational values of these chlorides . We first describe the agreement of our calculated values with the more reliable experimental values.…”
Section: Resultsmentioning
confidence: 83%
“…Highly correlated methods put it at ∼448 kJ/mol. 69 MnH (having a 7 ∑ + state) provides another example that also explains why we put less emphasis on the experimentally reported uncertainties than others do 11 (although some of these, in all fairness, are adequately estimated, many are probably not). The experimental value from the CRC Handbook 34 is 251 kJ/mol.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Another experimental estimate puts it at ∼500 kJ/mol, which is, on the other hand, too large using a similar analysis as the above. Highly correlated methods put it at ∼448 kJ/mol …”
Section: Resultsmentioning
confidence: 99%